Trends in Self Regulated Learning (SRL) in Indonesia Based on Web of Science (WOS) Data - Oktaviani, Herlina Ike; Kuswandi, Dedi (Edcomtech, 2024)
This study was conducted to reveal trends and research findings on the SRL approach published between 2008 and 2023, using descriptive review analysis to uncover trends related to article and journal performance, collaboration patterns, and research constituents. The findings indicate that the implementation of SRL increased significantly in 2018, coinciding with the shift to online learning due to the impact of the COVID-19 pandemic. SRL is highly relevant in digital-era learning as it fosters self-directed learning, time management, and the optimal use of technology, leading to more flexible and adaptive learning experiences. Therefore, this approach remained a trend through 2023, with the highest number of publications in educational research proceedings.